The physiological background of dwarf naked oats varieties: The preliminary results - Maciorowski, Robert; Werwiñska, Krystyna; Nita, Zygmunt; Stankowski, Slawomir (MTT, 2004)
In Poland the first naked oat cultivar Akt was registered in 1997 and the second variety Polar in 2002. Due to the high interest of farmers, the area of cultivation of naked oat quickly increased. To present ca 90000 ha. The factor restricting the cultivation of naked oat is a low grain yield. In the field trial conducted in 2003 on good rye complex soil, 23 strains of the dwarf naked oat, 2 traditional polish naked oats varieties (Akt, Polar) and the hulled variety Chwat were tested. The yield, yield components and biomass accumulation were compared with those of hulled oat. Photosynthetic activity was measured and LAI estimated. The traditional naked oat varieties Akt and Polar yielded 80 % of that in hulled Chwat, due to extremely dry conditions during spring and early summer in 2003. The yield of the dwarf strains of naked oat on an average was lower than traditional naked oat varieties. The plant density of the naked oats was lower than standard hulled oats. The higher productive tillering compensated lower plant density, hence the differences in the panicle density were not significant. The lower grain yield of the dwarf strains was caused by the panicle structure, mainly low number of grains per panicle, which was the result of low number of spikelets and the greater amount of fertile spikelets per panicle. Generally, the short stem strains had lower LAI, hence the canopy photosynthesis was lower. We found out the positive correlation between the LAI and the grain yield of dwarf strains. The main factor restricting the grain yield of the dwarf strains was low amount of assimilate partitioning to the grain. The harvest index this forms oscillated on the level ca 25 % and was significantly correlated with the grain yield. At the same term of measurement the dwarf cultivars had lower root biomass than standard cultivars. From that reason in the dry year they could not show their genetic ability for the high yielding. Scientific work financed by Agricultural University of Szczecin as a grant no. BW/IK/51/2003
Keywords: Ka; naked oat; dwarf varieties; grain yield; photosynthesis